FACTORS CONTRIBUTING TO POOR ADHERENCE TO ARVS AMONG HIV/AIDS PATIENTS ATTENDING ART CLINIC AT WAKISO HEALTH CENTER IV WAKISO DISTRICT. A CROSS-SECTIONAL STUDY . - NANYONGA , HOPE; Were , Amiri (Student’s Journal of Health Research Africa, 2023)
Background: The purpose of this study was to determine the factors contributing to poor adherence to ARVs among HIV/AIDS patients attending the ART clinic at Wakiso Health Centre, Wakiso District. Methodology: The study design used was the descriptive cross-sectional study design. Results: The results of the study showed that the individual-related factors were, busy schedules 53.65% and the workplace being very far from the area of picking drugs. The socio-economic related factors that contributed to poor adherence included; unemployment 54%, non-disclosure of respondent’s HIV sero status to their families 30%, negative support from family members 61.8% and the health facility- related factors that contributed to poor adherence to ARVs among HIV/AIDS patients included; longer- waiting time on the day of refill 54%, shortage of drugs at the health facility 66%, bad attitudes from health workers towards the respondents and lack of enough information on the drugs from health workers. Conclusion: Based on the overall findings the researcher concluded that busy schedules, workplace being very far from the area of picking drugs, unemployment, non-disclosure of HIV sero status, negative support from family members, longer- waiting time, shortage of drugs, bad attitudes from health workers and lack of enough information on drugs are the major factors contributing to poor adherence to ARVs among HIV/AIDS patients. Recommendation: Health education of patients by health workers should be done on dispensing, drug restocking should be regularly done to solve the lack of drugs, reminders should be used for the patients with busy schedules to solve forgetfulness, recruiting adequately trained health care workers in the ART clinic to reduce on the overload and solve the longer-waiting hours, and the government should provide simple jobs to HIV/AIDS patients to solve the unemployment issue and lack of transport fee.